Beneficial Effect of Growth Hormone Treatment on Health-Related Quality of Life in Children with Prader-Willi Syndrome: A Randomized Controlled Trial and Longitudinal Study - Bakker, Nienke E.; Siemensma, Elbrich P.C.; van Rijn, Marjon; Festen, Dederieke A.M.; Hokken-Koelega, Anita C.S. (Hormone research in paediatrics, 2015)
Background/Aims: Growth hormone (GH) treatment is beneficial for children with Prader-Willi syndrome (PWS), but data about health-related quality of life (HRQOL) and effects of GH treatment are scarce. We, therefore, investigated the effects of GH treatment on HRQOL in PWS children. Methods: In a randomized controlled GH trial including 26 PWS children and during an 11-year longitudinal GH study in 76 children, we annually assessed HRQOL recorded by patients and parents, using a generic questionnaire (DUX25), containing 4 subdomains (Physical, Home, Social, and Emotional) and a PWS-specific questionnaire (DUXPW). Results: At baseline, PWS children rated HRQOL similar to or higher than healthy and obese children. GH-treated children reported an increase in HRQOL in the Physical and Social subdomains and the DUXPW compared to untreated children. Parents reported an increase in the Physical and Emotional subdomains and borderline in the total DUX25 compared to parents of untreated children. During the 11 years of GH treatment, the Physical subdomain continued to improve, according to parents, whereas the Home, Social and Emotional subdomains, the total DUX25, and the DUXPW remained similar, according to children and parents. Conclusions: PWS children rated HRQOL equally to or better than healthy and obese children. HRQOL increased during GH treatment, in contrast to HRQOL of untreated children. This effect was sustained during long-term GH treatment. PWS children consider themselves quite happy, despite some difficulties related to the syndrome.